Pemberdayaan Guru dan Orang Tua dalam Menjaga Kesehatan Mental Anak Usia Dini melalui Psikoedukasi - Dzulfadhilah, Fitriani; H, Sri Rika Amriani; Lismayani, Angri; Rusmayadi, Rusmayadi; Asti, A. Sri Wahyuni (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2025)
Early childhood mental health is a key foundation in character building and successful ongoing emotional-social development. Mentally healthy children tend to be able to recognize and manage their emotions, establish positive social relationships, and adapt effectively to the surrounding environment. Teachers and parents, as the closest figure, have a central role in maintaining and detecting children's mental conditions early on. However, limited understanding and strong stigma towards children's mental health issues often become obstacles in providing the right response. This service activity aims to empower teachers and parents through psychoeducation to become more sensitive, responsive, and skilled in creating a supportive environment for children's mental health. The activity was carried out at Buah Hati Balang Punia Kindergarten, Gowa Regency, South Sulawesi, in May 2025, with 37 participants consisting of 1 principal, 6 teachers, and 30 parents. The implementation method included four stages: socialization and counseling, case study discussion, simulation and reflection, and evaluation through the implementation of pre-test and post-test. Results showed a significant increase in understanding, with an average pre-test score of 9.38 and post-test of 16.43. The paired sample t-test showed a significance value of p < 0.05. Psychoeducation proved to be an effective intervention in increasing the knowledge of teachers and parents as important partners in maintaining early childhood mental health